Handling the chemical part in large air pollution models - Brandt, Jorgen; Waśniewski, Jerzy; Zlatev, Zahari (Zielona Góra: Uniwersytet Zielonogórski)
Studying the trans boundary transport of air pollutants is an important environmental problem. Systems of partial differential equations are normally arising when mathematical models are used in the solution of this problem. The interrelations between the different air pollutants are rather complicated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka